(3TQM eNGQL GdMQas - (3GHf HQj , CHh GdMSf Ydj Hf eMeO Hf Ydj Hf GdMSjf GdQHGWj, GHf HQj,J (B730 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3CJhSd HYO GdMeO ddg Ydi eG ef ef EfYGeg hCcedG Ke Udi Gddg JJQi CHOkG Ydi GdfHi GdYQHi CMeOG s
(3BNQgG (B:s
(3hef jNQL hef CWQGagG eG CeJGR HGdEYLGe Yf NdGagG s
(3GdfSNI HgG MhGTs
(3fSNI YdjgG JUMjMGJs
(3cJHJ YfGhjfgG HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B220s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs